Between Reason and Revelation: Twin Wisdoms Reconciled. An Annotated English Translation of Nasir-i Khusraw’s Kitāb-i Jāmi‘ al-Ḥikmatayn By Eric Ormsby, trans. (London and New York: I.B. Tauris in association the Institute of Ismaili Studies, 2012. 292 pages.) (American Journal of Islam and Society, 2014)
Nasir-i Khusraw (d. 469/1077), who was appointed by the Fatimid imam al-Mustansir bi’llah (d. 487/1094) as the ḥujjat and chief dā‘ī for the region ofKhurasan, lived the later period of his life exiled in Badakhshan due to religiouspersecution. This treatise, a virtual summa of eleventh-century Ismailiphilosophical theology put forth in a question-and-answer format, deals withalmost all of the scientific and philosophical issues that occupied the mindsof the Isma‘ili mission of his time. The context is a reply to the amīr ofBadakhshan, Abu al-Ma‘ali ‘Ali ibn al-Asad (reign 462/1069), who had requestedNasir to explain Abu al-Haytham Ahmad ibn al-Hasan al-Jurjani’s (d.10th century) philosophical qaṣīdah. The text itself, originally edited by HenryCorbin and Mohammed Mu‘in in 1953, offers an alternative reading to LatimahParvin Peerwani’s clear but partial English translation, which was recentlypublished in the second volume of An Anthology of Philosophy ofPersia. Ibrahim al-Dasuqi Shata had translated the 1953 edition into Arabicin 1974, and Isabelle de Gastines’ French translation was made available in1990.Although the majority of the text is written in prose and not poetry, itwould still be pretentious in this short review to focus too critically on possiblealternative readings. Any reader with competence in the original language anda concern for specific passages now has several translations, along with theedited text, from which to make a critical comparison. The fact remains thatOrmsby has rendered a fluid and accurate translation that maintains the simplicityrequired to enable a broader audience to follow the complexity ofNasir’s ideas. An additional aid is also found in the copious footnotes, introductoryessay, index, and bibliography, all of which not only explain themany obscure points in Nasir’s treatise, but also suggest many areas for futureresearch.There is one question regarding the Persian text that does need additionalclarification: Ismail K. Poonawala pointed out in his review of Faquir M. Hunzai’sedition and translation of Nasir’s Gushāyish va Rahāyish (translated asKnowledge and Liberation: A Treatise on Philosophical Theology) that the ...